Procedimentos de abertura e fechamento de tópicos na interação em sala de aula - Santos, Francisco José Costa dos (2014)
This study is part of interactional perspective, focusing on Conversation Analysis theories, from the Textual Interactive Perspective and Text Linguistics . This research, from its guiding questions, aims at understanding the interaction between teacher and students in the process of the knowledge construction as well as at describing, analyzing and understanding aspects of topical organization speech in the classroom in elementary school, observing the opening and closing procedures of the speech topics in that particular space. Considering that the procedures for opening and closing of discursive topics occur through language marks, we tried to identify which speech marks are used in the opening and closing of the topics studied in the classroom, in interaction during the collaborative process of the discourse established between teacher and students. Therefore, this study is based on authors who analyze specific questions of the text in real context of language use: Koch (1993, 1999), Jubran et al (1991), Jubran (2006), Pine (2005), Penhavel (2010), Galembeck (2012), Barros (1991), Marcuschi (1986 , 1990, 1991 , 1998 , 1999, 2003 , 2004a), Kerbrat - Orecchioni (2006), Favero (1999, 2002) and Galvão (2004, 2010). As a methodology of investigation, the study is focused on the postulates of ethnographic research in order to carry out data collection, through audio and video recordings which were transcribed, according to the NURC project proposal, with some adaptations. Data analysis showed that the procedures for opening and closing of the speech topics occurred by the use of discourse markers, in particular the marker "then", allowing us to understand that these elements are important in the topical organization speech, contributing to ensure textual cohesion and coherence. We conclude that the organization of the discursive topic in the classroom occurs through events that support the explicitness of the content of teaching and learning, considering the diverse necessity of an institutional academic plan, whose main objective is the construction of knowledge